SISTEM INFORMASI AKADEMIK PADA MTS S NURUNNAJAH LOPAK AUR - Irma Suana; Jonifeak; Megawati, Merti (JURNAL AKADEMIKA)
With the goal of improving academic data management in decision-making in the educational environment, the Academic Information System is an application created for school administrative data processing needs. The waterfall technique will be used in this project to create a web-based academic information system for schools. It is believed that the creation of a web-based Siakad application will make it easier to manage academic data and make it even more efficient. On this web-based academic application, students can more quickly access and read grades as well as details about school events. It can be used at the school where the author conducts research as well as other schools that require it.